Design of a Web-Based E-Archive Information System for Project Report Documents at BPJN Aceh - Muhammad Ghifari Al-Wafi; Nurrizqa Nurrizqa; Nurrisma Nurrisma; Anni Zulfia; Annisa Karima (Sisfo: Jurnal Ilmiah Sistem Informasi, 2026)
Digital transformation in governance is driving the urgent need for a more modern and structured archive management system. The Aceh National Road Implementation Center (BPJN), especially the PPK 2.5 Subfield, still relies on conventional methods based on physical documents in managing project report archives, causing various problems such as difficulty tracing documents, risk of damage, and operational inefficiencies. Different from previous e-archive research which is generally applied to academic environments or general public services, this study presents the integration of the RAD method with the design of interfaces based on the needs of multi-role users in the context of managing technical reports of infrastructure projects in government agencies, a context that has not been widely studied in previous studies. This research aims to design an effective web-based e-archive information system equipped with an interactive user interface to increase the productivity of internal employees. The system development uses the Rapid Application Development (RAD) approach with the PHP programming language and MySQL database, and is built using the CodeIgniter framework with the Model-View-Controller (MVC) architecture. Data collection was carried out through field observation and structured interviews, while system validation used the black-box testing method. All 15 functional test scenarios were declared successful. A Likert scale user satisfaction evaluation involving three internal respondents showed a satisfaction rate of 86.7%, which falls into the excellent category.  The evaluation includes five aspects, namely ease of navigation, clarity of view, system response, design consistency, and general satisfaction, which are the basis for calculating the percentage. Given the limited number of respondents, further research is recommended to expand the number of samples and apply standard usability instruments such as the System Usability Scale (SUS) to strengthen the validity of the evaluation results. In addition, this study has not included comparative quantitative data before and after the implementation of the system, such as the measurement of document search time or the rate of archive loss in the manual mechanism compared to the new system, so the amount of efficiency improvement cannot be measured verified. System functionality validation also includes black-box testing, without additional testing such as stress testing, performance testing, or security testing, so the strength of the evidence for efficiency improvement claims is still limited and indicative. The developed system contains the features of uploading documents, searching archives, downloading reports, and managing user access rights. Although initial results show positive indications of system functionality and user satisfaction, the strength of the evidence for claims of improved archive management efficiency is still limited given the lack of comparative quantitative data before and after implementation and the new testing scope including black-box testing. The developed system still shows initial feasibility to be implemented gradually within BPJN Aceh, with a more comprehensive follow-up evaluation.